PERMAINAN TRADISIONAL GOBAK SODOR UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN KOLABORASI PADA SISWA KELAS V DI SD NEGERI RAWU - Cahya, Budiman Dwi; Taufik, M; Fajrudin, Lili (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine the implementation and describe teachers’ strategies in developing students’ communication and collaboration skills through the traditional game *gobak sodor*. The research employed a descriptive qualitative method. Data were collected through interviews, observations, and documentation. The findings indicated that the teacher’s planning was well-structured and aligned with students’ needs. The implementation of the *gobak sodor* game was effective in enhancing students’ communication and collaboration skills. Furthermore, the strategies applied by the teacher were proven to be effective in fostering these skills during the learning process. In conclusion, the integration of traditional games such as *gobak sodor* can serve as an effective approach to develop students’ communication and collaboration skills in elementary education.